PENERAPAN PERSIDANGAN SECARA ELEKTRONIK (E-LITIGASI) PADA PENGADILAN AGAMA CIKARANG - Lulu Tama Muliandini (2021)
E-litigation or electronic trial is a form of reformation carried out by the Mahkamah Agung (Supreme Court) in the field of technology and information in the justice system in Indonesia. Accordance with Article 13 of Law Number 48 of 2009 concerning Judicial Powers, all court hearings are open to the public, unless the law provides otherwise. However, a series of processes for examining and adjudicating cases by courts that are carried out electronically can cause uncertainty regarding the principle of being open to the public, especially when reading verdicts and decisions. The purpose of this study was to determine the process of implementing e-litigation and adjusting the principle of being open to the public in e-litigation carried out at the Pengadilan Agama Cikarang (Cikarang Religious Court). This research is an empirical legal research (juridical empirical) using statute approach, with the primary data obtained through direct research at the Pengadilan Agama Cikarang (Cikarang Religious Court) and the secondary data obtained through document study. The results showed that the e-litigation carried out at the Pengadilan Agama Cikarang (Cikarang Religious Court) was not much different between theory and practice, and e-litigation at the Pengadilan Agama Cikarang (Cikarang Religious Court) didn't fully fulfill the principle of being open to the public.